Development of Electronic Registry Operating Record of Shoulder and Elbow - Cholid Fauzi; Mochamad Nauval Ghassani; Chandriko Audito Rengganisworo; Silvia Nur Fadillah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The register book is used by the doctor to keep a record of the disease that finds and what action should be taken. This research goal is to develop e-registry web application has been created for registering shoulder and elbow surgery based on existing web based application. According to the problems mentioned, it is proposed to apply an e-registry shoulder and elbow surgery mobile-based using Flutter technology. The mobile application will be connected to the e-registry web application using the API concept. This application development uses the Incremental method with sequential development activities in two iterations. The research focused on developing mobile-based using reverse engineering method, and the finding of this research, using reverse engineering is more practical in its use. The type of test used to test the result of this result which is the application is unit testing with a black box approach which serves to determine the suitability of the input and output produced.